Situs inversus totalis with double superior vena cava: An unusual case report - Taşkent, İsmail and Danışan, Gürkan and Murat Aydın, Ayşe (Journal of Surgery and Medicine, 2019)
Situs inversus totalis (SIT) with double superior vena cava (SVC) is a rare congenital anomaly. Most cases are diagnosed incidentally after imaging for other reasons. Double SVC is usually asymptomatic, unless associated with other cardiac anomalies. A 22-year-old female patient with the complaints of cough, headache, weakness, and shortness of breath was admitted to the cardiology department. The patient, who was hospitalized with a diagnosis of pulmonary embolism and pulmonary hypertension, had a history of surgical repair of atrial septal defect and ventricular septal defect 7 years ago. Contrast-enhanced multislice computed tomography (CT) of the chest was obtained in our department. CT demonstrated SIT with double SVC, with the right SVC draining into the left atrium. The variations of anomalous venous connections accompanying cardiac anomalies should be fully defined before surgery with a combined imaging approach with echocardiography and CT.